Au cœur du debaa - Elena Bertuzzi (Ateliers d'Anthropologie)
In 2015, while I was in Mayotte writing an anthropological thesis on the debaa (Sufi-inspired chants and dances performed exclusively by women), I had the opportunity to create a multimedia installation that allowed me to present the data collected on this practice. This article looks back on the genesis of the project, the creation process, and issues linked to intangible heritage. It recounts the public’s experience and shows not only the relevance of the plastic transformation of ethnographic knowledge, which is often confined to the academic sphere, but also the boundaries with which researchers are confronted.